Study Of "Nazmi Aqoid" Work - Abdurahmon Latipov; Gulbahor Musayevna Surxonova (Zien Journals, 2023)
The article analyzes the commentaries on Abu Hafs Umar an-Nasafi's work "Aqoid un-Nasafi" and the controversy that the work "Nazmi Aqoid" belongs to Alisher Navoi.
Keywords: Famous; poet with the pseudonym; Turkish scientist professor Dr. Ahmed Sevgi